PENGEMBANGAN MOBILE LEARNING PENGUKURAN LISTRIK UNTUK SISWA PROGRAMKEAHLIAN TITL DI SMK - Tafrikhatin, Asni (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2018)
This study aims to developing mobile learning material electrical measurement. The research is a research and development that uses Waterfal research modell. Waterfall model development which consists of four stages: communication, planning, modelling, and construction. The subjects of this study were teachers and students of X class of Electrical Installation Study Program from SMK Negeri 3 Yogyakarta, SMK Negeri 1 Pundong, SMK Taman Siswa Yogyakarta, and SMK Muhammadiyah 3 Yogyakarta. The data were analyzed using descriptive. The result of mobile learning feasibility assessment according to validator was 80.30 and students equal to 85.59 from scale 100 so categorized as "Very Eligible". The result of mobile activity functionality evaluation according to validator was 83.25 and students equal to 86.66 from scale 100 so categorized "Very Eligible".